2020
DOI: 10.3389/fimmu.2020.574057
|View full text |Cite
|
Sign up to set email alerts
|

Vi-Vaccinations Induce Heterogeneous Plasma Cell Responses That Associate With Protection From Typhoid Fever

Abstract: Vi-polysaccharide conjugate vaccines are efficacious against cases of typhoid fever; however, an absolute correlate of protection is not established. In this study, we investigated the leukocyte response to a Vi-tetanus toxoid conjugate vaccine (Vi-TT) in comparison with a plain polysaccharide vaccine (Vi-PS) in healthy adults subsequently challenged with Salmonella Typhi. Immunological responses and their association with challenge outcome was assessed by mass cytometry and Vi-ELISpot assay. Immunization indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that polysaccharide-conjugate vaccines induce long lived antigen specific memory B cells (34). We have previously shown that Vi-TT vaccination induces Vi specific memory B cells which are significantly elevated above baseline 28 days after vaccination, while Vi-PS showed no significant change in memory B cell formation (25). Our data add to this and suggest that Vi specific memory B cells are not detectable in peripheral blood 19-23 months after Vi-TT vaccination.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies have shown that polysaccharide-conjugate vaccines induce long lived antigen specific memory B cells (34). We have previously shown that Vi-TT vaccination induces Vi specific memory B cells which are significantly elevated above baseline 28 days after vaccination, while Vi-PS showed no significant change in memory B cell formation (25). Our data add to this and suggest that Vi specific memory B cells are not detectable in peripheral blood 19-23 months after Vi-TT vaccination.…”
Section: Discussionsupporting
confidence: 69%
“…Vi-PS booster vaccination induced a significant increase in the frequency of Vi IgA ASCs between pre-boost (median = 3.0 ASCs/10 6 PBMCs) and 7 days post-boost (median = 7.7 ASCs/ 10 6 PBMCs), while no significant change was observed for ASCs producing anti-Vi IgG or IgM (Figure 6). In contrast, the initial Vi-TT vaccination induced significant increases in both Vi specific IgG and IgM ASCs (25). No data were collected on the anti-Vi IgA ASC response to primary conjugate vaccination.…”
Section: Igg Iga and Igm Peripheral Asc Responses To A Vi-ps Booster Vaccinationmentioning
confidence: 98%
“…Conversely, during infection with S. Typhi, the Vi capsule enables the bacterium to evade antibody-mediated neutrophil responses (30,31), and in vitro models of S. Typhi have shown its ability to evade the oxidative burst and phagosome maturation within monocytes and neutrophils after phagocytosis (32,33), ultimately resulting in bacterial dissemination. Vaccination with Vi-TCV however induces gut homing plasma cells that produce Vi-specific antibodies (34). Given the increase in ADNP following vaccination, these antibodies may have a role in activating Fc receptors on neutrophils to bring about phagocytosis, thus overcoming the natural ability of S. Typhi to evade neutrophilmediated responses.…”
Section: Discussionmentioning
confidence: 99%
“…High-dimensional cytometry, including mass cytometry and spectral flow cytometry, is a powerful technique to monitor immunity, identify cell subsets associated with diseases or potent responses to vaccines, and decipher the complex mechanisms of the immune response to vaccines (20)(21)(22)(23)(24)(25)(26)(27). However, the comparison and integration of different datasets generated at multiple sites and on different days is challenging, even when using the same technology.…”
Section: Comparing High Dimensional Cytometry Datasetsmentioning
confidence: 99%